COVID-19: Lessons from the Past to Inform the Future of Healthcare - Camilla Mattiuzzi; Giuseppe Lippi (COVID)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its global spread have left an indelible mark, disrupting multiple aspects of human life. It is therefore crucial to retrospectively analyze the factors that have contributed more to the initial inefficiency of the global response, thus enhancing preparedness and proactively addressing the risk of similar events occurring in the future. Critical areas were identified based on our expertise. Relevant bibliographic references were subsequently gathered through an open search of scientific databases to substantiate the concepts discussed in this article. The key issues that hindered an effective response to coronavirus disease 2019 (COVID-19) are numerous and multifaceted, and some of these will be critically examined in this article, including delayed identification of the pathogen, inadequate public health preparedness, inadequate therapeutic management, and deficiencies in laboratory diagnostics. From this analysis, key areas for improvement emerge to ensure more efficient responses to future health crises, including (i) enhancing and strengthening health information systems, (ii) improving pandemic preparedness and response planning, (iii) developing a resilient healthcare workforce, (iv) increasing investment in research and development, (v) expanding the use of telemedicine and digital health, (vi) ensuring universal access to healthcare, and (vii) improving public health communication and trust.